Developmental Origins of Kidney Disease: Why Oxidative Stress Matters? - Chien-Ning Hsu; You-Lin Tain (MDPI AG, 2020)
The "developmental origins of health and disease" theory indicates that many adult-onset diseases can originate in the earliest stages of life. The developing kidney has emerged as being particularly vulnerable to adverse in utero conditions leading to morphological and functional changes, namely renal programming. Emerging evidence indicates oxidative stress, an imbalance between reactive oxygen/nitrogen species (ROS/RNS) and antioxidant systems, plays a pathogenetic role in the developmental programming of kidney disease. Conversely, perinatal use of antioxidants has been implemented to reverse programming processes and prevent adult-onset diseases. We have termed this reprogramming. The focus of this review is twofold: (1) To summarize the current knowledge on oxidative stress implicated in renal programming and kidney disease of developmental origins; and (2) to provide an overview of reprogramming effects of perinatal antioxidant therapy on renal programming and how this may prevent adult-onset kidney disease. Although early-life oxidative stress is implicated in mediating renal programming and adverse offspring renal outcomes, and animal models provide promising results to allow perinatal antioxidants applied as potential reprogramming interventions, it is still awaiting clinical translation. This presents exciting new challenges and areas for future research.